Protective Effects of Cinnamaldehyde on the Oxidative Stress, Inflammatory Response, and Apoptosis in the Hepatocytes of Salmonella Gallinarum-Challenged Young Chicks. (5th July 2022) - Yin, Lizi; Hussain, Sajjad; Tang, Ting; Gou, Yuhong; He, Changliang; Liang, Xiaoxia; Yin, Zhongqiong; Shu, Gang; Zou, Yuanfeng; Fu, Hualin; Song, Xu; Tang, Huaqiao; et al.
Abstract : The development of novel therapeutics to treat multidrug-resistant pathogenic infections like Salmonella gallinarum is the need of the hour. Salmonella infection causes typhoid fever, jaundice, and Salmonella hepatitis resulting in severe liver injury. Natural compounds have been proved beneficial for the treatment of these bacterial infections. The beneficial roles of cinnamaldehyde due to its antibacterial, anti-inflammatory, and antioxidative properties have been determined by many researchers. However, alleviation of liver damage caused by S. gallinarum infection to young chicks by cinnamaldehyde remains largely unknown. Therefore, this study was performed to identify the effects of cinnamaldehyde on ameliorating liver damage in young chicks. Young chicks were intraperitoneally infected with S. gallinarum and treated with cinnamaldehyde orally. Liver and serum parameters were investigated by qRT-PCR, ELISA kits, biochemistry kits, flow cytometry, JC-1 dye experiment, and transcriptome analysis. We found that ROS, cytochrome c, mitochondrial membrane potential ( Ψ m), caspase-3 activity, ATP production, hepatic CFU, ALT, and AST, which were initially increased by Salmonella infection, significantly (P < 0.05 ) decreased by cinnamaldehyde treatment at 1, 3, and 5 days postinfection (DPI). In addition, S. gallinarum infection significantly increased proinflammatory gene expression ( IL-1β, IL-6, IL-12, NF-κB, TNF-α, and MyD-88 ) and decreased the expression of anti-inflammatory genes ( IL-8, IL-10, and iNOS ); however, cinnamaldehyde reverted these effects at 1, 3, and 5 DPI. Transcriptome analysis showed that S. gallinarum modulates certain genes of the AMPK-mTOR pathway for its survival and replication, and these pathway modulations were reversed by cinnamaldehyde treatment. We concluded that cinnamaldehyde ameliorates inflammation and apoptosis by suppressing NF-K β /caspase-3 pathway and reverts the metabolic changes caused by S. gallinarum infection via modulating the AMPK-mTOR pathway. Furthermore, cinnamaldehyde has antibacterial, anti-inflammatory, antioxidative, and antiapoptotic properties against S. gallinarum- challenged young chicks and can be a candidate novel drug to treat salmonellosis in poultry production.